Penguatan Kapasitas Ibu Balita dan Kader Posyandu melalui Edukasi Environmental Enteric Dysfunction sebagai Faktor Risiko Stunting - Sanjaya, Ayling; Budiono Raharjo; Anna Lewi Santoso (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Stunting remains a major public health challenge in Indonesia because it adversely affects physical growth, cognitive development, and future human capital. Besides inadequate nutrition, stunting is associated with Environmental Enteric Dysfunction (EED), a chronic disorder of the small intestinal mucosa caused by poor environmental hygiene that impairs nutrient absorption. Limited knowledge of EED among mothers of children under five and Posyandu cadres hinders effective stunting prevention. This community service program aimed to strengthen their capacity through education on EED as a risk factor for stunting. The program was conducted in Rungkut District, Surabaya, through educational material development, pre-test, interactive lectures, discussions, post-test, and evaluation. A total of 66 mothers and 27 Posyandu cadres participated, with 100% attendance. Maternal knowledge improved, as the proportion of participants with good knowledge increased from 22.7% to 30.8%, while poor knowledge decreased from 77.3% to 69.2%. Among Posyandu cadres, good knowledge increased from 21.7% to 22.2%, accompanied by better understanding of EED, hygiene, sanitation, and balanced nutrition. Overall, the program strengthened the capacity of mothers and Posyandu cadres to support community-based stunting prevention through health education.